2017
DOI: 10.3390/ma10101171
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites for Machining Tools

Abstract: Machining tools are used in many areas of production. To a considerable extent, the performance characteristics of the tools determine the quality and cost of obtained products. The main materials used for producing machining tools are steel, cemented carbides, ceramics and superhard materials. A promising way to improve the performance characteristics of these materials is to design new nanocomposites based on them. The application of micromechanical modeling during the elaboration of composite materials for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…The results showed that an addition of less than 0.1% concentration of CNTs increased hardness, strength, and Young’s Modulus, but led to a decrease in grain size. This was due to the binder recrystallisation process being hindered due to the nanotube particles at grain boundaries, which also prevented coating oxidation [ 5 ]. Coatings on PcBN tools are typically 2–3 μm in thickness, therefore they cannot compensate for a poor substrate with surface defects and nonhomogeneous surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that an addition of less than 0.1% concentration of CNTs increased hardness, strength, and Young’s Modulus, but led to a decrease in grain size. This was due to the binder recrystallisation process being hindered due to the nanotube particles at grain boundaries, which also prevented coating oxidation [ 5 ]. Coatings on PcBN tools are typically 2–3 μm in thickness, therefore they cannot compensate for a poor substrate with surface defects and nonhomogeneous surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been some interesting works focused on how to improve the rigidity and strength of WC‐Ni hardmetals . Inter alia, some scientists improved the mechanical performance of WC‐based hardmetals by developing submicrometer or even nanometer WC powders, and/or by mixing certain additives of high rigidity/strength into the WC matrix . Also, specific fast sintering techniques and/or grain growth inhibitors (GGIs) have been used to develop ultrafine hardmetals .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-fiber-reinforced polymer composites (CFRPs) have been increasingly used during the past decades due to their potential for significant weight saving [ 1 , 2 , 3 ]. Historically, thermoset resins have been used as matrix for CFRPs [ 4 , 5 , 6 ], but the requirements for thermoplastic matrix have been elevated during the past decade [ 7 , 8 , 9 ]. Compared with thermosets, thermoplastics are inherently tough [ 10 , 11 , 12 ], recyclable, and have an unlimited shelf life [ 13 ].…”
Section: Introductionmentioning
confidence: 99%